Is legalization of drugs needed? Selected social and psychological aspects - Marciniak, Beata (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
The aim of the article is to present some aspects of social and psychological phenomena of drug abuse in relation to a demand for drug legalization. There are many factors behind drug abuse by a young person, as for example: a pathological family, influence of a peer group or a weak will and failure to cope with various problems. These examples are supported by presented in the text statements of the addicted. They present how difficult it is to get rid of addiction and how quickly a need for a bigger amount of a drug appears.